Proporsi Margarin-Mentega Pada Pembuatan Getuk Banava Oven - Arya Naufal Zafir; Any Sutiadiningsih; Sri Handajani; Ila Huda Puspita Dewi (Pusat Riset dan Inovasi Nasional, 2024)
Getuk Banava Oven is an innovative product that is processed by mixing banana getuk and cassava getuk with margarine fat and butter and then placing it in the oven. Getuk Banava oven is made from banana, jackfruit, cassava and margarine and butter. The aim of this research is to determine the organoleptic properties of getuk banava oven including texture, color, taste and aroma and to determine the nutritional content of getuk banava oven products. This research is in the form of an experiment. The data collection technique used was observation through 5 trained panelists and 25 semi-trained panelists who were assisted by an observation sheet assessing the 0-15cm line. Data analysis using One Way ANNOVA. The results of research tests show that there is an influence of color, taste and texture; there is no color influence on the getuk banava oven product; has a protein nutritional content of 8.90%, carbohydrates of 53.25%, fat of 2.65%, water content of 30.61%, and fiber of 3.65